2021
DOI: 10.3390/rs13112112
|View full text |Cite
|
Sign up to set email alerts
|

WRF-Chem Simulation for Modeling Seasonal Variations and Distributions of Aerosol Pollutants over the Middle East

Abstract: Atmospheric aerosols and dust have become a challenge for urban air quality. The presented study quantified seasonal spatio-temporal variations of aerosols, tropospheric ozone, and dust over the Middle East (ME) for the year 2012 by using the HTAP emission inventory in the WRF-Chem model. Simulated gaseous pollutants, aerosols and dust were evaluated against satellite measurements and reanalysis datasets. Meteorological parameters, temperature, and wind vector were evaluated against MERRA2. The model showed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…However, it did not match the performance of the other two models in simulating particulate matter concentrations. Shahid et al [15] simulated the seasonal spatial and temporal variations of aerosols, tropospheric ozone, and dust over the Middle East (ME) in 2012 using the WRF-Chem model, and achieved better simulation results. Do et al [16] used the WRF-Chem model to simulate the meteorological variables in winter and summer in northern Vietnam in 2014, along with the local PM 2.5 and PM 10 concentrations, and showed that although the simulation results had a good spatial and temporal consistency with observations, the amount of day-to-day variability at each observation site was difficult to capture, which may be related to either the model itself or the input emissions data.…”
Section: Introductionmentioning
confidence: 99%
“…However, it did not match the performance of the other two models in simulating particulate matter concentrations. Shahid et al [15] simulated the seasonal spatial and temporal variations of aerosols, tropospheric ozone, and dust over the Middle East (ME) in 2012 using the WRF-Chem model, and achieved better simulation results. Do et al [16] used the WRF-Chem model to simulate the meteorological variables in winter and summer in northern Vietnam in 2014, along with the local PM 2.5 and PM 10 concentrations, and showed that although the simulation results had a good spatial and temporal consistency with observations, the amount of day-to-day variability at each observation site was difficult to capture, which may be related to either the model itself or the input emissions data.…”
Section: Introductionmentioning
confidence: 99%
“…Regional air quality models have been essential tools for scientifically understanding the distribution of emissions sources, transport and transformation (Yarragunta et al, 2020;Shahid et al, 2021;Jena et al, 2021;Du et al, 2022;Kumar et al, 2022). For regional modelling studies, emission inventories are essential for reflecting the emission inputs into the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods are difficult to use for large areas due to the limited number of observation stations. Therefore, some studies estimated spatial distributions of dust concentrations over a large area by using air quality models, including the Weather Research and Forecasting model coupled with Chemistry (WRF-Chem) [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Although air quality models can reproduce the dust concentrations over a large region, most of these studies mainly concentrated on specific dust episodes (e.g., Rizza et al, 2017;Karagulian et al, 2019;Karegar et al, 2019) [41][42][43] or a short-term simulations (e.g., Shahid et al, 2021) [40]. China is one of the major contributors to global dust aerosols [27,44].…”
Section: Introductionmentioning
confidence: 99%